Transplantation for Alcohol-related Liver Disease: Is It Fair?. (11th December 2017) - Mellinger, Jessica L; Volk, Michael L
Abstract: Aims: Alcohol-related liver disease (ALD) is the second leading cause of liver transplantation performed in the USA and Europe. We aimed to provide a narrative review of the major ethical issues governing transplantation for ALD. Methods: We performed a narrative review of the ethical concepts in organ allocation for ALD, including alcoholic hepatitis. Results: Ethical concerns regarding organ allocation for ALD involve issues of urgency, utility and justice. Post-transplant outcomes for ALD patients are good and ethical considerations limiting organs solely because of alcohol etiology do not bear scrutiny. Conclusion: ALD will continue to be a major cause for liver failure. The main criteria for transplant in ALD should be the patient's risk of return to harmful drinking, alongside standard assessments of physical and psychosocial fitness for transplant.